C/EBPγ is a critical negative regulator of LPS‐/IgG immune complex‐induced acute lung injury through the downregulation of C/EBPβ‐/C/EBPδ‐dependent C/EBP transcription activation. Issue 10 (12th August 2020) - Yan, Chunguang; Zhang, Lanqiu; Yang, Lei; Zhang, Qi; Wang, Ximo
Abstract: Acute lung injury (ALI) and its more severe form, acute respiratory distress syndrome are life‐threatening diseases. Despite recent advances in intensive care medicine, the mortality is still as high as 50%, which stems from our insufficient understanding of the underlying mechanisms of the diseases. The roles of C/EBPβ and C/EBPδ have been extensively investigated in LPS‐ and IgG immune complexes‐stimulated acute lung injury. However, the effect of C/EBPγ, belonging to the same family as C/EBPβ and C/EBPδ, on ALI has not been elucidated. Our previous data have shown that during LPS‐/IgG immune complexes‐induced ALI, the DNA binding activities of C/EBPγ are obviously reduced. In the present study, we determine whether ALI induced by LPS and IgG immune complexes is affected by C/EBPγ. We find that adenovirus‐mediated C/EBPγ expression in the lung tissue alleviates LPS‐/IgG immune complexes‐stimulated acute pulmonary damage through reducing vascular permeability changes and recruitment of neutrophils into alveolar spaces, which might be linked to a decrease in the production of pro‐inflammatory mediators, such as TNF‐α and IL‐6. Moreover, our data obtained from macrophages in vitro are consistent with the in vivo results. In terms of mechanisms, C/EBPγ might inhibit LPS‐/IgG immune complexes‐mediated inflammation via alleviating C/EBPβ and C/EBPδ transcription activities as reflected by luciferase assays. However, the NF‐κB‐dependent production of pro‐inflammatory mediators is not affected by C/EBPγ. Taken together, C/EBPγ suppresses LPS‐ and IgG immune complexes‐induced pro‐inflammatory mediators' production through the downregulation of C/EBP but not NF‐κB activation, leading to the subsequent attenuation of ALI. Collectively, our data provide an insight into the critical role of C/EBPγ in acute lung injury.